2019
DOI: 10.1093/forsci/fxz045
|View full text |Cite
|
Sign up to set email alerts
|

Molecular and Pathogenic Characteristics of Paecilomyces formosus, a New Causal Agent of Oak Tree Dieback in Iran

Abstract: Oak dieback is one of the most important diseases that presently affects the Kermanshah oak forests (West Iran). During the period from 2013 to 2015, oak trees exhibiting branch dieback were sampled, and fungal colonies resembling those of the Paecilomyces sp. were obtained from diseased tissues. Based on morphology, physiology, and phylogeny of the internal transcribed spacer rDNA, all isolates were identified as Paecilomyces formosus. Pathogenicity tests in vivo were made on 2-year-old seedlings, potted Q. b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(20 citation statements)
references
References 24 publications
1
19
0
Order By: Relevance
“…Species of Paecilomyces were found in acidic habitats and can tolerate microaerophilic conditions; however, P . formosus can also be found causing plant diseases and as an opportunistic pathogen in humans [ 76 78 ]. Basidiomycota taxa needs substrates rich in nutrients (such as wood and dung) to grow in cave environments, and species included in Rigidoporus are mainly found as plant pathogens [ 5 , 72 , 79 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Species of Paecilomyces were found in acidic habitats and can tolerate microaerophilic conditions; however, P . formosus can also be found causing plant diseases and as an opportunistic pathogen in humans [ 76 78 ]. Basidiomycota taxa needs substrates rich in nutrients (such as wood and dung) to grow in cave environments, and species included in Rigidoporus are mainly found as plant pathogens [ 5 , 72 , 79 ].…”
Section: Discussionmentioning
confidence: 99%
“…Species identified in Aspergillus section Polypaecilum are mainly treated as xerotolerant/xerophilic and halotolerant/halophilic and found in built environments [74], although a species was recently described from marine sediments in Mexico [75]. Species of Paecilomyces were found in acidic habitats and can tolerate microaerophilic conditions; however, P. formosus can also be found causing plant diseases and as an opportunistic pathogen in humans [76][77][78]. Basidiomycota taxa needs substrates rich in nutrients (such as wood and dung) to grow in cave environments, and species included in Rigidoporus are mainly found as plant pathogens [5,72,79].…”
Section: Plos Onementioning
confidence: 99%
“…4 ) ( A. alternata ( 28 ), A. flavus (postharvest) ( 29 , 30 ), B. austrostipae ( 31 ), Chaetomium globosum ( 32 ), C. cladosporioides ( 33 ), C. lunata ( 34 ), Curvularia sp. ( 34 ), P. formosus ( 35 , 36 ), P. albobadia ( 37 ), Periconia macrospinosa ( 38 ), R. oryzae ( 39 ), R. kalkhoffii ( 40 ), S. commune ( 40 ), and X. badia (decay fungus) ( 41 , 42 ), with three of these not previously reported in the United States: B. austrostipae , P. formosus , and X. badia . These pathogens represent disease agents of cereal crops, fruits/vegetables, trees, and postharvest pathogens, as well as decayers ( 29 , 33 , 40 , 42 ).…”
Section: Resultsmentioning
confidence: 87%
“…Microscopically, it was observed that the conidiophores had verticillate branches, septate hyphae, hyaline, 3 to 6 phialids, and conidia chains that were fusiform or ellipsoidal in shape with a smaller size, i.e 1.8-2.1 X 2.3-2.8 µm. Sabernasab et al (2019) also showed that the growth of Paecilomyces colonies reached 2.5 cm with a yellow colony surface after being grown in PDA media for seven days. Microscopically, this study found branching conidiophores with one or more phialids, and chain conidia with cylindrical to ellipsoidal shapes were seen measuring 3.53-6.58 (16.3) X 2.01-3.80 (2.75) µm.…”
Section: Stain Fungi Isolates and Their Morphological Characteristicsmentioning
confidence: 85%